Akselerasi Pemanfaatan Aplikasi Pengelolaan Keuangan Digital Sektor UKM di Jawa Timur dan Nusa Tenggara Barat - Meithiana Indrasari; Eko Pamuji; M Adhi Prasnowo; Muhajir Sulthonul Aziz; Moch. Subechi Nurcahyo (Prapanca : Jurnal Abdimas, 2022)
The acceleration of digital transformation in the Small and Medium Enterprises (SME) sector is the government's big target and plan until 2024. In its growth, SMEs must become one of the main driving wheels in economic development and development. SMEs must carry out financial management. In the era of sophisticated technology, everything is done manually, can be solved digitally, for example recording and bookkeeping using bookkeeping applications. So it is necessary to implement a Digital Entrepreneurship Academy (DEA) training program for Digital Financial Management. The implementation method by providing training with an offline class curriculum of 2 days 13 Hours Meeting with the results of providing new insights and understanding for participants to be able to compete globally in their respective business sectors. It was explained that 95% of the participants considered that the material was relevant to the problems faced by the participants and the benefits of the training could be judged to have a decent level of sustainability to continue to be implemented.